G484S amino acid substitution in lanosterol 14-alpha demethylase (ERG11) is related to fluconazole resistance in a recurrent Cryptococcus neoformans clinical isolate - Rodero, Laura (2003)
Five sequential Cryptococcus neoformans isolates recovered from an AIDS patient with recurrent meningitis were analyzed. Four isolates were fluconazole susceptible, while the fifth isolate developed fluconazole resistance. Analysis of the 14- lanosterol demethylase gene (ERG11) showed a point mutation in the resistant strain responsible for the amino acid substitution G484S.